Lung function in athletes and non-athletes aged 13-15 years - Ni Komang Diah Saputri; Ayu Setyorini Mestika Mayangsari; Ida Bagus Subanada (Paediatrica Indonesiana, 2018)
Background Regular sports or physical training contributes in increasing the body's pulmonary function. The increase of pulmonary function is determined by the strength of respiratory muscle, thoracic compliance, upper respiratory system resistance, and pulmonary elasticity. Objective To compare pulmonary function between athletes and non-athletes aged 13-15 years. Methods This is a cross-sectional analytical study conducted onnior high school students aged 13-15 years throughout June to August 2017. Participants are classified as athletes from particular sports and non-athletes. Assessment of pulmonary function was done using a spirometry test, in which each subject was asked to inhale and exhale in a particular method. Parameters assessed include vital capacity (VC), forced vital capacity (FVC), expiratory volume in 1 second (FEV1), forced expiratory flow (FEF) and FEV1/FVC. Differences in lung function between athletes and non-athletes were analyzed using independent T-test. Results There were 60 athletes and 60 non-athletes included in this study. The mean age of athletes and non-athletes were 13.38 (SD 0.99) years old and 13.70 (SD 0.76) years old, respectively. The statistically significant differences in mean lung function parameters between athletes and non-athletes were as follows: VC: 85.03% vs. 79.41%, respectively (P=0.035); FVC: 95.66% vs. 88.43%, respectively (P=0.016); FEV1: 102.10% vs. 94.28%, respectively (P=0.016); and FEV1/FVC: 105.95% vs. 102.69%, respectively (P=0.011). However, there were no statistically significant differences in the means of FEF 25-75% between the two groups (P>0.05). Conclusions Parameters of lung function in athletes are in general significantly higher than in non-athletes.